Common Causes of Visual Impairment Among Sixth Grade Students in Boyer Ahmad city - Shahram Bamdad (Iranian South Medical Journal, 2017)
Background: In line with the implementation of primary health care, Knowing the factors causing visual impairment is very helpful among children and students among population of each district. That's why in this study, we intend to study common causes of visual impairment in sixth grade elementary students in Boyer Ahmad city and we compared the results with similar studies.